"Thousands of New Sankaras": Resistance and Struggle in Burkina Faso. Issue 3 (December 2015) - Hagberg, Sten
This article analyses recent political developments in Burkina Faso, particularly the failed coup d'état in September 2015. The coup was led by the former president's security forces (RSP), comprised of 1, 300 heavily equipped and well-trained soldiers. The RSP took the president and government hostage and declared the coup d'état. The coup was condemned by most Burkinabe, civil society organisations, trade unions, and political parties, as well as by the international community. Across the country, people mobilised in popular resistance and civil disobedience. RSP soldiers patrolled and shot live rounds into neighbourhoods, while residents built barricades. Resistance mounted in Ouagadougou and elsewhere in the country, and after a few days it became clear that the coup would fail. In this article, I describe the courage and determination of the Burkinabe people in the face of the coupists and thereby show that popular resistance and revolutionary struggle are part and parcel of Burkinabe political culture. In conclusion, I discuss the prospects for a veritable democratic breakthrough in Burkina Faso.